Validity and Reliability of the Turkish Form of the Eating Behavior Scale for Children - Meltem Kürtüncü; Nurten Aslan (Dokuz Eylul University, 2020)
Backgraund: Eating behavior is a complex biopsychosocial behavior involving eating and eating time. Objectives: The aim of this study was to determine the validity and reliability of Turkish Children's Eating Behavior Inventory which was evaluated by families with disabled children. Methods: Translation and back-translation were used for the adaptation of the scale. Content validity index was employed for content validity, while exploratory and confirmatory factor analyses for construct validity. Cronbach's alpha coefficient and item-total correlation coefficient were used to test the reliability of the scale. Test-retest reliability of the scale was 72, internal consistency and construct validity were determined by data collected from 190 parents with disabled children living with their spouses with at least 2 children. Results: The Cronbach's alpha value of the scale was .77 and the scale was generally accepted as reliable. According to factor analysis; The scale was gathered under 5 factors and the explanatory coefficient was 65.05%. Kaiser-Meyer-Olkin (KMO) sample adequacy measurement value .71 is used to evaluate the suitability of the data for factor analysis. The Bartlet Sphericity Test was x2 / df = 1370.545 / 171, p <.001, and the data were considered appropriate for factor analysis. Acceptable and good fit according to confirmatory factor analysis (p=.001; p< .01). Conclusion: The Turkish version of the Children's Eating Behavior Inventory was a valid and reliable scale for assessing the eating behaviors of children with disabilities with two parents and at least two siblings.